2017
DOI: 10.1039/c7cp04603k
|View full text |Cite
|
Sign up to set email alerts
|

TMAO mediates effective attraction between lipid membranes by partitioning unevenly between bulk and lipid domains

Abstract: Under environmental duress, many organisms accumulate large amounts of osmolytes - molecularly small organic solutes. Osmolytes are known to counteract stress, driving proteins to their compact native states by their exclusion from protein surfaces. In contrast, the effect of osmolytes on lipid membranes is poorly understood and widely debated. Many fully membrane-permeable osmolytes exert an apparent attractive force between lipid membranes, yet all proposed models fail to fully account for the origin of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 66 publications
6
44
0
Order By: Relevance
“…In an earlier study by Sukenik et al, 24 TMAO was reported to dehydrate bilayer systems under excess water conditions when TMAO is in a phase-separated aqueous phase. Here we show that the trend is reversed in the absence of excess water, which is the relevant boundary condition in the stratum corneum.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In an earlier study by Sukenik et al, 24 TMAO was reported to dehydrate bilayer systems under excess water conditions when TMAO is in a phase-separated aqueous phase. Here we show that the trend is reversed in the absence of excess water, which is the relevant boundary condition in the stratum corneum.…”
Section: Discussionmentioning
confidence: 95%
“…It was previously shown that the partitioning of co-solutes within multilamellar membrane systems is sensitive to the co-solutes' preferential interactions with the membrane surfaces. 23,24 It is therefore likely that co-solute/membrane preferential interactions are of relevance also for the membranes' short-range repulsion. 53 Fig.…”
Section: Simulation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Far simpler approaches found in nature involve the use of small polar (osmolyte) molecules, such as sugars, free amino acids, urea, glycerol, and TMAO (13,14,16,18,50,(54)(55)(56)(57). The mechanism by which these small molecules protect the biological systems against osmotic stress is different from that of the dehydrins and may also be different between the different osmolyte compounds (29,32,58). The last question addressed in this article concerns the similarities and differences between dehydrin Lti30 and small polar osmolytes in their effects on lipid membrane systems at varying hydration conditions.…”
Section: Dehydration-induced Phase Transitions: Comparison Between Dehydrin Lti30 and Small Osmolytesmentioning
confidence: 99%
“…The osmolytes used for these studies, urea and TMAO, are typically not found in plants but serve as model compounds to illustrate general molecular mechanisms. Urea and TMAO were chosen as model osmolytes because their effects on lipid membranes in dry conditions have previously been well characterized (29)(30)(31)(32).…”
mentioning
confidence: 99%